Business Spending on Research and Development and its Relationship to Invention and Innovation (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The paper deals with the problem of business spending on research and development and their relation to innovation activities. It is focused on R&D in the business sector as a crucial part of the innovation system. R&D expenditure can be seen as the main precondition of successful innovation. However, the successful transformation of R&D investment into invention or innovation cannot be guaranteed. Our main aim is to examine the relationship between business R&D expenditure, invention and innovation in the long-run. We also examine the level of business R&D expenditure in EU countries. The long-run causalities have been tested by using panel cointegration approach on the macro-level panel data for EU countries. The scope of inventions is proxied by the share of firms introducing product or service innovation as well as the number of patents registered. Based on our results, there appears to be a positive causal effect of business R&D expenditure on patenting in the long-run. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.